Chasing the past : geopolitics of memory on the margins of modern Greece - Sintès, Pierre (Sociétés contemporaines., 2019)
Since 2008, Greece has been at the centre of European current affairs due to the financial and economic crisis. However, it should not be forgotten that before the current crisis the political upheavals of the early 1990s and the collapse of Marxist-inspired regimes had already radically transformed the face of the country. These transformations have been seen as a return of the Balkans' question, raising issues of border disputes and migration, minorities and national inclusion. They have had far-reaching consequences on the relations between Greek society and its peripheries, and what some have deemed to be its destabilising diversity. In this context, the material presented in this book examines the strengthening of discourses of belonging which draw legitimacy from a glorification of the past and tradition. The fieldwork carried out over the past 15 years on the fringes of Greece has focused on groups who were stigmatised and distanced from standard definitions of Greekness. It provides an original perspective on the changes that the country has undergone in recent decades. The question of the nation-state's future is raised through close observation on the local scale, leading to a debate about the relationship between areal and reticular territory within the framework of globalisation. This book also aims to provide non-Francophone readers with access to research carried out on these issues in France, shifting the focus of Balkan Anglophone specialists for whom French publications remain a distant province.